การเตรียมเซรั่มบำรุงผิวหน้าเพื่อความขาวกระจ่างใสด้วยไดไฮโดรออกซีเรสเวราทรอลจากแก่นมะหาด - ธวัลรัตน์ ยิ้มน้อย (จุฬาลงกรณ์มหาวิทยาลัย, 2022)
Products containing Cannabidiol (CBD) are gaining popularity in beauty and wellness industry. However, its color can change easily. The stability of CBD was studied by three parameters, which are humidity, temperature, and exposure to air, but it cannot retain the color of CBD-containing products. This study was focused on two parameters: types of antioxidants and the pH value of products. The color change of CBD containing cosmetic formulations with the addition of various antioxidants including Tris(tetramethylhydroxypiperidinol) citrate (TTMHP), Benzotriazolyl dodecyl p-cresol (BTDC), Pentaerythrityl Tetra-di-t-butyl Hydroxyhydrocinnamate (PTH), Tocopheryl acetate (TAC), Sodium metabisulfite (SMS) and Butylated hydroxytoluene (BHT) has been investigated in this work. In addition, effects from pH values of the formulation have also been included. The study was carried out by observing the color change by eye periodically on formulation kept under accelerated condition of 45 degrees Celsius. The results showed that products with pH 4 had the least color change and products that added BHT retained their color.